Nano-cellulose reinforced environment-friendly biodegradable straw and preparation method thereof
By using the composite technology of chitin nanofibers and bacterial cellulose hydrolysates in the straw, combined with zein and modified nanocellulose fibers, a nanocellulose-enhanced environmentally friendly biodegradable straw was prepared, which solved the problem of insufficient antibacterial performance, flexibility, mechanical properties and biodegradability of the straw, and realized an environmentally friendly, safe and durable straw product.
Patent Information
- Application Number
- CN202411747089.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-03-07
AI Technical Summary
Existing straws have shortcomings in antibacterial properties, flexibility, mechanical properties and biodegradability, resulting in problems such as non-anti-bacterial, prone to rupture, and polluting the environment.
By mixing chitin nanofibers with bacterial cellulose hydrolysate, and introducing zein dispersion and modified nanocellulose filaments into the nanocellulose membrane, nanocellulose enhancement and environmentally friendly biodegradation pipettes were prepared using technologies such as sonication and autoclaving.
The antibacterial performance, flexibility enhancement, mechanical performance enhancement and biodegradation function of straws is achieved, and the problem of traditional straws polluting the environment is solved.
Smart Images

Figure CN119570119A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of straw preparation, and in particular to a nanocellulose reinforced environmentally friendly biodegradable straw and a preparation method thereof. Background Art
[0002] As people's awareness of environmental protection continues to increase, the problem of plastic pollution has received more and more widespread attention from society. Traditional plastic straws, due to their difficult-to-degrade characteristics, have caused serious pollution to the marine ecosystem and terrestrial environment. Therefore, degradable products have become an indispensable environmentally friendly alternative.
[0003] Bacterial cellulose has extremely high crystallinity, purity and fiber strength. It is an ideal substrate for preparing high-performance composite materials. Chitin has excellent biodegradability and good antibacterial function. By compounding chitin nanofibers with bacterial cellulose, it can not only improve the strong hydrophilicity of bacterial cellulose, but also give it certain antibacterial properties. Therefore, a nanocellulose-reinforced environmentally friendly biodegradable straw and its preparation method are extremely important.
[0004] 1. Patent document CN114190747B discloses a bacterial cellulose-based edible straw and a preparation method thereof. The above patent realizes that the bacterial cellulose-based straw has the characteristics of high strength, high toughness, and no microplastic release, but the above patent cannot achieve the function of improving the antibacterial performance of the straw.
[0005] 2. Patent document CN112297515B discloses a degradable straw of micro-nano hybrid fibers and its preparation. The above patent realizes that the hybrid cellulose straw has the properties of being pure natural, high-performance, low-cost and degradable, but the above patent cannot achieve the function of improving the flexibility of the straw.
[0006] 3. Patent document CN109734947B discloses a fully biodegradable straw straw and a method for preparing the same. The above patent achieves that the prepared straw is safe to use, can be fully degraded, and will not cause pollution to the environment. However, the above patent cannot achieve the function of improving the mechanical properties of the straw.
[0007] 4. Patent document CN114806113B discloses a heat-resistant and antibacterial PLA fully biodegradable straw and a preparation method thereof. The above patent improves the heat resistance of the straw and improves the mechanical properties of the straw, but the above patent cannot achieve the biodegradation function of the straw.
[0008] In summary, the above patents cannot achieve the function of improving the antibacterial performance of the straw, cannot achieve the function of improving the flexibility of the straw, cannot achieve the function of improving the mechanical properties of the straw, and cannot achieve the biodegradation function of the straw, resulting in the problem that the straw is not antibacterial, is easy to break, and pollutes the environment;
[0009] To this end, the present application proposes a nanocellulose reinforced environmentally friendly biodegradable straw and a preparation method thereof, which can improve the antibacterial properties of the straw, improve the flexibility of the straw, improve the mechanical properties of the straw, and realize the biodegradation function of the straw. Summary of the invention
[0010] The purpose of the present invention is to provide a nanocellulose reinforced environmentally friendly biodegradable straw and a preparation method thereof, so as to solve the technical problems proposed in the above background technology that the antibacterial performance of the straw cannot be improved, the flexibility of the straw cannot be improved, the mechanical properties of the straw cannot be improved, and the biodegradation function of the straw cannot be achieved, resulting in the straw being not antibacterial, easy to break, and polluting the environment.
[0011] To achieve the above object, the present invention provides the following technical solution: a nanocellulose reinforced environmentally friendly biodegradable straw, comprising a nanocellulose film, and a preparation method of the nanocellulose film comprises the following steps:
[0012] (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring;
[0013] (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0014] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly;
[0015] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
[0016] Preferably, the method for preparing the bacterial cellulose hydrolysate comprises the following steps:
[0017] (1) breaking the bacterial cellulose film using a homogenizer, adding the broken bacterial cellulose fragments into distilled water, and stirring to uniformly disperse the bacterial cellulose to obtain a bacterial cellulose suspension;
[0018] (2) adding cellulase to the bacterial cellulose suspension, placing the mixture in a 50°C water bath, reacting for 2 h, transferring the mixture of bacterial cellulose and cellulase to a microwave synthesizer, and performing enzymatic hydrolysis for 15 min;
[0019] (3) placing the enzymatically hydrolyzed mixed solution in a water bath at 100° C. for 10 min to inactivate the enzyme, placing the inactivated mixed solution in a centrifuge tube for centrifugation, and collecting the hydrolyzate layer on the upper layer of the centrifuge tube to obtain the bacterial cellulose hydrolyzate.
[0020] Preferably, the method for preparing the zein dispersion comprises the following steps:
[0021] (1) adding zein nanoparticles to an ethanol solution, and stirring with a magnetic stirrer until the zein nanoparticles are completely dissolved in the ethanol solution;
[0022] (2) Under stirring conditions, the thymol-loaded powder is poured into an ethanol solution containing zein, deionized water is added to the solution, and the mixture is stirred evenly. The solution is placed in a rotary evaporator to remove ethanol and a small amount of water, thereby obtaining a zein dispersion.
[0023] Preferably, the method for preparing the modified nanocellulose fibrils comprises the following steps:
[0024] (1) placing nanocellulose fibrils in anhydrous ethanol, adding ammonia water, tetraethyl orthosilicate, and a silane coupling agent respectively, and stirring the mixed solution evenly using a magnetic stirrer;
[0025] (2) placing the mixed solution in an ultrasonic disperser for reaction, and after the ultrasonic reaction is completed, centrifuging the mixed solution to obtain modified nanocellulose fibrils.
[0026] 5. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 1, characterized in that the mass ratio of the chitin nanofiber suspension to the bacterial cellulose hydrolyzate is 6:4.
[0027] Preferably, the method for preparing the bacterial cellulose film comprises the following steps:
[0028] (1) adding sucrose to a reaction vessel filled with distilled water, stirring until the sucrose is dissolved, placing the reaction vessel in a water bath at 100° C., pouring green tea into the reaction vessel, soaking for 15 minutes, filtering to remove green tea residue, cooling to room temperature, inoculating red tea fungi into the reaction vessel, and fermenting for 14 days to obtain a bacterial cellulose film;
[0029] (2) The bacterial cellulose film is taken out from the fermentation liquid, and immersed in distilled water for 48 hours. The immersed bacterial cellulose film is taken out and rinsed with sodium hydroxide solution. The sodium hydroxide solution is replaced every 12 hours, and repeated 3 times to obtain a pure white and transparent bacterial cellulose film. The bacterial cellulose film is treated with glacial acetic acid until it is neutral to obtain a purified bacterial cellulose film.
[0030] Preferably, the silane coupling agent is selected from one of n-octyltrimethoxysilane, vinyltrimethoxysilane and hexadecyltrimethoxysilane.
[0031] Preferably, the method for preparing the nanocellulose fibrils comprises the following steps:
[0032] (1) adding sodium hydroxide to a reaction container, adding deionized water to the reaction container to fully dissolve the sodium hydroxide to form a uniform alkaline solution, adding sodium hypochlorite solution to the alkaline solution, and stirring uniformly;
[0033] (2) adding bamboo powder into a reaction container, placing the reaction container in a 40° C. water bath, taking out the reaction container after 2 hours and cooling it to room temperature, and washing the reaction mixture with deionized water to obtain cellulose pulp;
[0034] (3) The washed cellulose pulp is sent to an ultrafine particle crusher for crushing, and a high-pressure microfluidizer is used to homogenize the treated cellulose pulp to obtain nanocellulose fibrils.
[0035] Preferably, the preparation method comprises the following steps:
[0036] S1, taking out the dried nanocellulose membrane from the tray and cutting it according to the size and shape of the straw to obtain a membrane sheet;
[0037] S2, evenly coating the sodium alginate solution on the surface of the membrane, winding the membrane to form a basic shape of a straw, and immersing the wound membrane in a calcium lactate solution to perform ion exchange;
[0038] S3. The wound membrane sheet that has undergone ion exchange treatment is taken out and dried to obtain a straw.
[0039] Preferably, the preparation method further comprises the following steps:
[0040] S31. Trim the straws, remove excess parts, trim both ends and outer surfaces of the straws, and perform quality inspection, packaging and storage on the straws.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The present invention improves the antibacterial performance of the straw through the composite effect of chitin nanofibers, bacterial cellulose hydrolyzate and modified nanocellulose fibrils, effectively inhibits bacteria that the straw may come into contact with during use, reduces the risk of bacterial contamination, and ensures the health and safety of users;
[0043] 2. The present invention achieves the function of improving the flexibility of the straw by introducing bacterial cellulose hydrolyzate and zein dispersion into the nanocellulose membrane, thereby improving the flexibility and anti-rupture performance of the nanocellulose membrane;
[0044] 3. The present invention improves the mechanical properties of the straw by modifying the nanocellulose fibrils, thereby enhancing the compatibility and interaction between the nanocellulose fibrils and other components, forming a more uniform and dense composite structure, and improving the overall mechanical properties of the nanocellulose film;
[0045] 4. The present invention realizes the biodegradation function of the straw by preparing biodegradable chitosan nanofibers, bacterial cellulose and other materials into nanocellulose film, thereby solving the problem of traditional plastic straws polluting the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a schematic diagram of the preparation process of the nanocellulose membrane of the present invention;
[0047] Figure 2 This is a schematic diagram of the preparation process of the chitosan nanofiber suspension of the present invention;
[0048] Figure 3 This is a schematic diagram of the preparation process of bacterial cellulose hydrolysate of the present invention;
[0049] Figure 4 This is a schematic diagram of the preparation process of the zein dispersion of the present invention;
[0050] Figure 5 This is a schematic diagram of the preparation process of the modified nanocellulose fibrils of the present invention;
[0051] Figure 6 This is a schematic diagram of the preparation process of the bacterial cellulose membrane of the present invention;
[0052] Figure 7 This is a schematic diagram of the preparation process of nanocellulose fibrils of the present invention;
[0053] Figure 8 Schematic diagram of the silane coupling agent of the present invention. DETAILED DESCRIPTION
[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1, please refer to Figure 1 and Figure 8 A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0056] (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring;
[0057] (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0058] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly;
[0059] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for autoclave treatment, pouring the autoclaved solution into a tray, placing the tray in an oven for drying treatment, and obtaining a nanocellulose membrane;
[0060] Furthermore, chitosan has good biodegradability. The chitosan molecular structure contains amino cations, which can combine with phospholipid anions in the bacterial cell wall to form a polymer film on the cell wall surface, interfering with the normal transfer and transportation of substances inside and outside the cell, making it have certain antibacterial properties. Chitosan nanofibers have the characteristics of high strength and high modulus. After mixing with bacterial cellulose hydrolysate, they can significantly improve the mechanical strength, toughness and tensile strength of the nanocellulose membrane. Chitosan nanofibers can increase the water barrier of the nanocellulose membrane to a certain extent and improve the strong hydrophilic tendency of the bacterial cellulose hydrolysate.
[0061] Example 2, please refer to Figure 1 , Figure 3 and Figure 6A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0062] (1) using a homogenizer to break up a bacterial cellulose film, adding the broken bacterial cellulose fragments into distilled water, stirring to uniformly disperse the bacterial cellulose to obtain a bacterial cellulose suspension, adding cellulase to the bacterial cellulose suspension, placing the mixture in a 50° C. water bath, reacting for 2 h, transferring the mixture of bacterial cellulose and cellulase to a microwave synthesizer, performing an enzymatic hydrolysis reaction for 15 min, placing the enzymatically hydrolyzed mixture in a water bath at 100° C. for 10 min, performing enzyme inactivation treatment, placing the inactivated mixture in a centrifuge tube for centrifugation, collecting the hydrolyzed liquid layer on the upper layer of the centrifuge tube, and obtaining a bacterial cellulose hydrolyzate;
[0063] (2) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, gradually adding glacial acetic acid into the chitosan dispersion while stirring, pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0064] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly;
[0065] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for autoclave treatment, pouring the autoclaved solution into a tray, placing the tray in an oven for drying treatment, and obtaining a nanocellulose membrane;
[0066] Furthermore, bacterial cellulose hydrolyzate will form a three-dimensional network structure during the preparation process. This structure has good flexibility and elasticity, thus making the straw have good softness. The three-dimensional network structure can buffer external pressure to a certain extent and prevent the straw from breaking or deforming during use. In the preparation process of nanocellulose membrane, bacterial cellulose hydrolyzate can reduce the shrinkage and deformation of the membrane material during the drying process, thereby further improving the softness and stability of the straw.
[0067] Example 3, please refer to Figure 1 and Figure 4 A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0068] (1) adding zein nanoparticles to an ethanol solution, stirring with a magnetic stirrer until the zein nanoparticles are completely dissolved in the ethanol solution, pouring the loaded thymol powder into the ethanol solution containing zein under stirring, adding deionized water to the solution, stirring evenly, placing the solution in a rotary evaporator, removing ethanol and a small amount of water, and obtaining a zein dispersion;
[0069] (2) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, gradually adding glacial acetic acid into the chitosan dispersion while stirring, pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0070] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly;
[0071] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for autoclave treatment, pouring the autoclaved solution into a tray, placing the tray in an oven for drying treatment, and obtaining a nanocellulose membrane;
[0072] Furthermore, zein has a certain regulatory effect on the absorption of water. By adding zein dispersion, the water-blocking ability of the nanofiber membrane can be increased and the hydrophilic defect of bacterial cellulose hydrolysate can be improved. During the preparation process of the nanocellulose membrane, the protein molecules in the zein dispersion can interact with the nanofibers to form a more stable cross-linked structure, thereby improving the durability of the nanocellulose membrane.
[0073] Example 4, please refer to Figure 1 , Figure 5 and Figure 8 A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0074] (1) placing nanocellulose fibrils in anhydrous ethanol, adding ammonia water, tetraethyl orthosilicate, and a silane coupling agent respectively, stirring the mixed solution evenly with a magnetic stirrer, placing the mixed solution in an ultrasonic disperser for reaction, and after the ultrasonic reaction is completed, centrifuging and washing the mixed solution to obtain modified nanocellulose fibrils;
[0075] (2) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, gradually adding glacial acetic acid into the chitosan dispersion while stirring, pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0076] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly;
[0077] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for autoclave treatment, pouring the autoclaved solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane;
[0078] Furthermore, the modification of the nanocellulose fibrils can improve the hydrophobicity of the nanocellulose fibrils, thereby increasing the water resistance of the nanocellulose membrane, avoiding deformation or rupture of the straw due to liquid penetration, increasing the service life of the straw, and rewriting the nanocellulose fibrils to have better flexibility, plasticity and mechanical strength, which can enhance the overall mechanical properties of the nanocellulose membrane. The modification of the nanocellulose fibrils can increase the cross-linking points between the nanocellulose fibrils, thereby forming a stable network structure, which improves the nanocellulose membrane's resistance to deformation at high temperatures, and then enhances the thermal stability of the straw.
[0079] Example 5, please refer to Figure 1 and Figure 7 A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0080] (1) adding sodium hydroxide to a reaction container, adding deionized water to the reaction container, fully dissolving the sodium hydroxide to form a uniform alkaline solution, adding a sodium hypochlorite solution to the alkaline solution, stirring evenly, adding bamboo powder to the reaction container, placing the reaction container in a 40° C. water bath, taking out the reaction container after 2 hours and cooling it to room temperature, washing the reaction mixture with deionized water to obtain cellulose slurry, sending the washed cellulose slurry to an ultrafine particle grinder for pulverization, and homogenizing the treated cellulose slurry with a high-pressure microfluidizer to obtain nanocellulose fibrils;
[0081] (2) breaking the bacterial cellulose film using a homogenizer, adding the broken bacterial cellulose fragments into distilled water, stirring to uniformly disperse the bacterial cellulose to obtain a bacterial cellulose suspension, and mixing the chitin nanofiber suspension with the bacterial cellulose suspension to obtain a mixed solution;
[0082] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and respectively adding the mixed solution, zein dispersion and nanocellulose fibrils into the solution, and stirring evenly;
[0083] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
[0084] Example 6, please refer to Figure 1 and Figure 2 A nanocellulose-reinforced environmentally friendly biodegradable straw comprises a nanocellulose film, and a method for preparing the nanocellulose film comprises the following steps:
[0085] (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring;
[0086] (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0087] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, adding the mixed solution into the solution, and stirring evenly;
[0088] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
[0089] Comparative Example 1, a nanocellulose-reinforced environmentally friendly biodegradable straw, comprising a nanocellulose film, wherein the preparation method of the nanocellulose film comprises the following steps:
[0090] (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring;
[0091] (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0092] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution and zein dispersion into the solution, respectively, and stirring evenly;
[0093] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
[0094] Comparative Example 2, a nanocellulose-reinforced environmentally friendly biodegradable straw, comprising a nanocellulose film, wherein the preparation method of the nanocellulose film comprises the following steps:
[0095] (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring;
[0096] (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution;
[0097] (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution and modified nanocellulose fibrils into the solution, respectively, and stirring evenly;
[0098] (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
[0099] Performance Testing
[0100] Test 1 Tensile strength performance test: The nanocellulose films prepared in Example 1, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 were cut into samples with a size of 50 mm × 5 mm, and the samples were clamped on the upper and lower clamps of a tensile testing machine, and the tensile load when the samples broke was recorded.
[0101] Test 2 Antibacterial performance test: Example 1, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 were cut into samples with a size of 20 mm×20 mm, the samples were placed in a Staphylococcus aureus suspension, and the OD value of the bacterial suspension was measured after 12 hours.
[0102] Table 1 Test results of tensile strength performance test
[0103] Example Tensile strength(MPa) Example 1 186.35 Example 5 168.38 Example 6 145.56 Comparative Example 1 153.78 Comparative Example 2 157.37
[0104] Table 2 Test results of antibacterial performance test
[0105] Example OD value of bacterial solution Example 1 0.45 Example 5 0.57 Example 6 0.81 Comparative Example 1 0.72 Comparative Example 2 0.64
[0106] Working principle: Nanocellulose membrane and its components are derived from natural materials, with good biocompatibility and degradability. After use, the straw can be naturally degraded to reduce pollution to the environment. The amino cations contained in chitosan can penetrate into the bacteria and interact with the negatively charged substances in the bacteria, hindering the normal growth and reproduction of bacteria and improving the antibacterial properties of the nanofiber membrane.
[0107] The modified nanocellulose fibrils form a dense network structure in the nanocellulose membrane, providing a physical barrier for bacteria, hindering the penetration and reproduction of bacteria, and at the same time improving the mechanical strength of the nanocellulose membrane. After the bacterial cellulose hydrolysate is mixed with the chitin nanofibers, the fiber fragments in the bacterial cellulose hydrolysate are intertwined with the chitin nanofibers to form a denser and stronger composite structure, thereby forming a more stable and stronger nanocellulose membrane, improving the overall mechanical properties of the nanocellulose membrane, thereby improving the durability and service life of the straw;
[0108] Zein has good film-forming properties and biocompatibility. Zein dispersion plays a bonding and toughening role in the nanocellulose membrane. The various component materials work synergistically in the nanocellulose membrane to jointly improve the mechanical properties and biodegradability of the membrane.
[0109] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A nanocellulose-reinforced environmentally friendly biodegradable straw, characterized by: The invention comprises a nanocellulose film, wherein the preparation method of the nanocellulose film comprises the following steps: (1) adding an appropriate amount of chitosan powder into distilled water, and uniformly dispersing the chitosan powder in the distilled water by stirring to form a preliminary chitosan dispersion, and gradually adding glacial acetic acid into the chitosan dispersion while stirring; (2) pouring the stirred and mixed dispersion into a homogenizer for homogenization, transferring the homogenized dispersion into a high-pressure microfluidizer for high-pressure treatment to obtain a chitosan nanofiber suspension, and mixing the chitosan nanofiber suspension with a bacterial cellulose hydrolyzate to obtain a mixed solution; (3) adding agar and sodium alginate into distilled water, heating and stirring until completely dissolved to form a uniform mixed solution, and adding the mixed solution, zein dispersion and modified nanocellulose fibrils into the solution respectively, and stirring evenly; (4) placing the uniformly mixed solution in an ultrasonic crusher for ultrasonic treatment, pouring the mixed solution after ultrasonic crushing into an autoclave for steam pressing, pouring the steam pressed solution into a tray, placing the tray in an oven for drying, and obtaining a nanocellulose membrane.
2. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 1, characterized in that: The preparation method of the bacterial cellulose hydrolysate comprises the following steps: (1) breaking the bacterial cellulose film using a homogenizer, adding the broken bacterial cellulose fragments into distilled water, and stirring to uniformly disperse the bacterial cellulose to obtain a bacterial cellulose suspension; (2) adding cellulase to the bacterial cellulose suspension, placing the mixture in a 50°C water bath, reacting for 2 h, transferring the mixture of bacterial cellulose and cellulase to a microwave synthesizer, and performing enzymatic hydrolysis for 15 min; (3) placing the enzymatically hydrolyzed mixed solution in a water bath at 100° C. for 10 min to inactivate the enzyme, placing the inactivated mixed solution in a centrifuge tube for centrifugation, and collecting the hydrolyzate layer on the upper layer of the centrifuge tube to obtain the bacterial cellulose hydrolyzate.
3. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 1, characterized in that: The preparation method of the zein dispersion comprises the following steps: (1) adding zein nanoparticles to an ethanol solution, and stirring with a magnetic stirrer until the zein nanoparticles are completely dissolved in the ethanol solution; (2) Under stirring conditions, the thymol-loaded powder is poured into an ethanol solution containing zein, deionized water is added to the solution, and the mixture is stirred evenly. The solution is placed in a rotary evaporator to remove ethanol and a small amount of water, thereby obtaining a zein dispersion.
4. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 1, characterized in that: The preparation method of the modified nanocellulose fibrils comprises the following steps: (1) placing nanocellulose fibrils in anhydrous ethanol, adding ammonia water, tetraethyl orthosilicate, and a silane coupling agent respectively, and stirring the mixed solution evenly using a magnetic stirrer; (2) placing the mixed solution in an ultrasonic disperser for reaction, and after the ultrasonic reaction is completed, centrifuging the mixed solution to obtain modified nanocellulose fibrils.
5. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 1, characterized in that: The mass ratio of the chitin nanofiber suspension to the bacterial cellulose hydrolyzate is 6:
4.
6. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 2, characterized in that: The method for preparing the bacterial cellulose film comprises the following steps: (1) adding sucrose to a reaction vessel filled with distilled water, stirring until the sucrose is dissolved, placing the reaction vessel in a water bath at 100° C., pouring green tea into the reaction vessel, soaking for 15 minutes, filtering to remove green tea residue, cooling to room temperature, inoculating red tea fungi into the reaction vessel, and fermenting for 14 days to obtain a bacterial cellulose film; (2) The bacterial cellulose film is taken out from the fermentation liquid, and immersed in distilled water for 48 hours. The immersed bacterial cellulose film is taken out and rinsed with sodium hydroxide solution. The sodium hydroxide solution is replaced every 12 hours, and repeated 3 times to obtain a pure white and transparent bacterial cellulose film. The bacterial cellulose film is treated with glacial acetic acid until it is neutral to obtain a purified bacterial cellulose film.
7. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 4, characterized in that: The silane coupling agent is selected from one of n-octyltrimethoxysilane, vinyltrimethoxysilane and hexadecyltrimethoxysilane.
8. The nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 4, characterized in that: The method for preparing the nanocellulose fibrils comprises the following steps: (1) adding sodium hydroxide to a reaction container, adding deionized water to the reaction container to fully dissolve the sodium hydroxide to form a uniform alkaline solution, adding sodium hypochlorite solution to the alkaline solution, and stirring uniformly; (2) adding bamboo powder into a reaction container, placing the reaction container in a 40° C. water bath, taking out the reaction container after 2 hours and cooling it to room temperature, and washing the reaction mixture with deionized water to obtain cellulose pulp; (3) The washed cellulose pulp is sent to an ultrafine particle crusher for crushing, and a high-pressure microfluidizer is used to homogenize the treated cellulose pulp to obtain nanocellulose fibrils.
9. A method for preparing a nanocellulose-reinforced environmentally friendly biodegradable straw, applicable to the nanocellulose-reinforced environmentally friendly biodegradable straw and its preparation method as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1, taking out the dried nanocellulose membrane from the tray and cutting it according to the size and shape of the straw to obtain a membrane sheet; S2, evenly coating the sodium alginate solution on the surface of the membrane, winding the membrane to form a basic shape of a straw, and immersing the wound membrane in a calcium lactate solution to perform ion exchange; S3. The wound membrane sheet that has undergone ion exchange treatment is taken out and dried to obtain a straw.
10. The method for preparing a nanocellulose-reinforced environmentally friendly biodegradable straw according to claim 9, characterized in that: The preparation method further comprises the following steps: S31. Trim the straws, remove excess parts, trim both ends and outer surfaces of the straws, and perform quality inspection, packaging and storage on the straws.
Citation Information
Patent Citations
A fully biodegradable straw and its preparation method
CN109734947B
A biodegradable straw made of micro / nano hybrid fibers and its preparation
CN112297515B
A bacterial cellulose-based edible straw and its preparation method
CN114190747B
A heat-resistant, antibacterial, fully biodegradable PLA straw and its preparation method
CN114806113B